Effects of feeding enriched-olive cake on milk quality, metabolic response, and rumen fermentation and microbial composition in mid-lactating Holstein cows - A. Amato; L. Liotta; C. Cavallo; C. L. Randazzo; A. Pino; S. Bonacci; M. Frisina; A. Procopio; F. Litrenta; V. Floridia; A. R. Di Rosa; M. Oteri; et al. (Italian Journal of Animal Science, 2024)
The aim of this study was to evaluate the effects of supplementing OC enriched in polyphenols (EOC) to mid-lactating Holstein cows on milk quality, metabolic response, and rumen fermentation and microbiota. Twenty multiparous Holstein dairy cows (10 cows/group) were enrolled for 30 d in two homogeneous groups according to milk yield, days in milking, parity, and body condition score. The control group (CTR) received no supplemented concentrate, whereas the EOC group received concentrate with a 7% inclusion of EOC. Milk and blood samples were collected at 0 d and 30 d of treatment, while rumen fluid samples were collected after 30 d of treatment. Overall, the dietary supplementation of EOC did not affect milk yield and its quality, rumen pH, and rumen VFA. However, milk of EOC cows had lower C10:0, C12:0, C14:0, and C16:0 content, and greater C18:0, C18:1 cis-9, and C18:2 n6 content, compared with CTR cows. Regarding the rumen microbiota composition, EOC diet increased the relative abundance of Bacteroidales_RF16_group, Absconditabacteriales_(SR1), and Fibrobacteracea in the rumen. On cow’s metabolism, EOC cows showed lower blood haptoglobin and greater ferric reducing antioxidant power (FRAP), cholesterol, and Zn levels compared with CTR cows. The supplementation of EOC led to a milder low-grade inflammatory response of cows and a positive modulation of cholesterol synthesis (probably at both intestinal and hepatic level). Supplementing EOC modulated rumen microbiota and improved the lipid profile of milk. Thereby, OC may be considered a valid feed to be included in the dairy cow’s diet leading to a positive effects on dairy cattle metabolism (less low-grade inflammatory response and oxidative stress) and at the same time giving an added value to the milk with a better profile of the fatty acids.